2018
DOI: 10.1080/03079457.2018.1492090
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene transcription in the trachea, Harderian gland, and trigeminal ganglia of chickens inoculated with virulent infectious laryngotracheitis virus (ILTV) strain

Abstract: The objective of this study was to determine how cytokine transcription profiles correlate with patterns of infectious laryngotracheitis virus (ILTV) replication in the trachea, Harderian gland, and trigeminal ganglia during the early and late stages of infection after intratracheal inoculation. Viral genomes and transcripts were detected in the trachea and Harderian gland but not in trigeminal ganglia. The onset of viral replication in the trachea was detected at day one post-infection and peaked by day three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Briefly, immediately after the homogenization of CALT and HG samples in 1 mL of TRIzol (Thermo Fisher, Waltham, MA, USA), 200 μL of chloroform was added and the samples were centrifuged at 4 °C for 15 min at 12,000× g . Total RNA was further purified from the upper aqueous phase using the RNeasy kit (QIAGEN, Valencia, CA, USA) as previously described [12]. To eliminate DNA contamination, the eluted RNA was treated with TURBO DNA-free™ (2 to 4 units/per reaction) (Ambion, Carlsbad, CA, USA) for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, immediately after the homogenization of CALT and HG samples in 1 mL of TRIzol (Thermo Fisher, Waltham, MA, USA), 200 μL of chloroform was added and the samples were centrifuged at 4 °C for 15 min at 12,000× g . Total RNA was further purified from the upper aqueous phase using the RNeasy kit (QIAGEN, Valencia, CA, USA) as previously described [12]. To eliminate DNA contamination, the eluted RNA was treated with TURBO DNA-free™ (2 to 4 units/per reaction) (Ambion, Carlsbad, CA, USA) for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the purity and concentration of RNA per sample, optical density ratios (260/280 and 260/230) were obtained using the NanoDrop™ 2000c (Thermo Fisher Scientifics, Waltham, MA, USA). Previous to cDNA synthesis, a real time PCR reaction that amplifies the chicken β-actin gene was performed to ensure the absence of residual DNA in the eluted RNA using primers previously described [12]. The β-actin gene amplification reaction was performed in a 20 μL volume—10 μL of SYBR ® Select Master Mix (2X) (Life Technologies, Carlsbad, CA, USA), 1 μL of 5 μM of each primer, 5 μL of template and 3 μL of nuclease free water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments using bursectomized chickens showed that ILTV antibodies are not protective [ 28 , 29 ], and it has been demonstrated in thymectomized chickens that cell-mediated immunity is critical against ILT [ 30 ]. Additionally, a correlation has been observed between increased pro-inflammatory and anti-inflammatory cytokine gene transcription and enhanced inflammatory cell recruitment, significant tissue damage, and decreased ILTV replication in the trachea [ 32 ].…”
Section: Introductionmentioning
confidence: 99%